Essential health services delivery in South Africa during COVID-19: Community and healthcare worker perspectives - Lalla-Edward, Samanta T.; Mosam, Atiya; Hove, Jennifer; Erzse, Agnes; Rwafa-Ponela, Teurai; Price, Jessica; Nyatela, Athini; Nqakala, Sizwe; Kahn, Kathleen; Tollman, Stephen; Hofman, Karen; Goldstein, Susan (Frontiers in Public Health, 2022)
Background Between May 2020 and February 2022, South Africa’s health system bore strain as it battled mitigating the coronavirus pandemic. The country’s pandemic response was scrutinized. This period also brought into focus pre-existing shortcomings in the healthcare system and its governing bodies. Contextually, there is a paucity in literature on the experiences of healthcare providers and users. This study aimed to contribute information on COVID-19, with the intention of providing guidance on preparing for future infectious disease outbreaks. Methods Cross sectional explorative methodology was employed using semi-structured interviews and focus group discussions with community members (CM) and healthcare workers (HCW) from two South African study sites: a) rural Bushbuckridge (run by Agincourt Health and Socio-Demographic Surveillance Site) and b), Regions D and F in Johannesburg Metropole. Results After interviewing 42 CMs and 43 HCWs, it emerged that mandated process changes while minimizing COVID-19 exposure, necessitated healthcare personnel focusing on critical care treatment at the expense of less acute ones. COVID-19 isolation protocols, extensive absenteeism, and HCWs with advanced skills being perceived as more adept to treat COVID-19 patients contributed to HCWs experiencing higher workloads. Fears regarding contracting and transmitting COVID-19, suffering financial losses, and not being able to provide adequate advice to patients were recurrent themes. Dissemination of relevant information among healthcare facility personnel and communities suffered due to breakdowns in communication. Conclusion Concessions and novel strategies to avail medication to patients had to be created. Since providence was lacking, the government needs to formulate health intervention strategies that embrace health literacy, alternate methods of chronic medication dispensation, improved communication across health care platforms, and the use of telehealth, to circumvent the threats of possible further infectious disease outbreaks.